PERANCANGAN SISTEM ASPEK KEUANGAN MIZAFIQ QUA OKSI CIPASUNG TASIKMALAYA - Ahmad Zamakhsyari Sidiq; Iwan Kurniawan; Siti Nurjanah (Cipasung Techno Pesantren: Jurnal Ilmiah, 2022)
Mizaviq Qua Oksi is one of the businesses engaged in refill depot services. Based on the results of a survey conducted by researchers, the Mizaviq Qua Oksi refill depot business has not been able to analyze the financial aspects, so it is difficult to understand in projecting the balance sheet, cash flow and profit and loss. In this case the owner does not know the financial condition of a certain period. If this happens, it is feared that the depot will experience slow development. Realizing these situations and conditions, an innovation and direction is needed to process the financial aspects of business activities for the Mizaviq Qua Oksi refill depot in accordance with accounting standards. The study was conducted to determine the company's financial condition / position and business prospects. The design of the financial aspect system is in the form of a report consisting of working capital, investment, operational costs, COGS, profit and loss, cash flow, balance sheet, BEP and investment feasibility analysis.The final results of this study indicate that the company's financial condition is good with net profit increasing every year, while the overall results of the investment feasibility analysis show that the investment carried out by the company is not feasible because it does not match the criteria.